The clinical and immunomodulatory effects of green soybean extracts - Katayanagi, Yuki; Yasui, Kensuke; Ikemoto, Hiroyuki; Taguchi, Kyoko; Fukutomi, Ryuta; Isemura, Mamoru; Nakayama, Tsutomu; Imai, Shinjiro (Food chemistry, 2013)
► Green soybean extract regulate the production of BAFF and APRIL in mouse spleen cells. ► Green soybean extract suppressed the TDI-induced nasal mucosa secretion. ► The symptom scores for pollinosis were improved by the green soybean extract. The present study was performed to investigate the immune-modulating activities of extracts from green soybean (Glycine max) in a 2,4-toluene diisocyanate (TDI)-inducing guinea pig rhinitis model and a human trial study for allergic rhinitis. Hot water extracts of green soybean were chosen for animal experimentation on the basis of their ability to regulate the production of B cell-activating factor of the TNF family and a proliferation-inducing ligand in mouse spleen cells. Green soybean extracts significantly decreased the levels of ovalubumin (OVA)-specific IgE in mice and significantly suppressed the TDI-induced nasal mucosa secretion. An open-label human pilot study was performed on 16 subjects, using Japanese cedar pollinosis. The symptom scores for Japanese cedar pollinosis were better in the long-term green soybean extracts intake group than in the withdrawal short-term intake group. Green soybean extracts had great potential as an orally active immune modulator for the treatment of various allergic diseases.